Mega-trials. Extraordinariness and outbursts in the judiciary ritual for crimes against humanity (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article is an approach to the legal proceedings invol- ving crimes against humanity from an ethnographic pers- pective, that is to say, an approach that goes from the intui- tive to the counterintuitive in order to answer the following question: “what do we see when we see a hearing of a crimes against humanity case?”. By making the distinction between my first impressions of extraordinariness and outbursts, I will deal with the judiciary ritual of the mega-trials, elabo- rating on a description that allows fully understanding the concept within its legal framework.
Keywords: Mega-trials; Extraordinariness; Judiciary ritual; politic outbursts.